Investigation on experimental load spectrum for high and low cycle combined fatigue test - Rongqiao Wang; Jiaming Wei; Dianyin Hu; Xiuli Shen; Jiang Fan (Propulsion and Power Research, 2013)
As the outfield load spectrum is so complicated that it cannot be used directly for test study in laboratory. This paper presents a method to determine load spectrum for high and low cycle combined fatigue of turbine mortise at elevated temperature through experimental and numerical method. First of all, the low cycle load spectrum with duration time is determined through cumulative damage rule. The rain flow counting method is applied to obtain main cycles and sub cycles, and then the stress cycle is converted into pulsation cycle (stress ratio=0) based on the S-N curve and the Goodman curve; Secondly, three groups of different amplitudes tests are established to determine the high cycle amplitude. Finally, another three groups of the high-low combined cycle fatigue (HLCCF) tests for turbine mortise of a certain type engine are carried out. The results show that the macro and micro failure modes are identical with outfield's, which verifies the accuracy of the conversion method.